High-rate GNSS positioning for precise detection of dynamic displacements and deformations: methodology and case study results - Paziewski, Jacek; Sieradzki, Rafal; Baryla, Radoslaw (International Conference “Environmental Engineering”, 2017)
The monitoring of static and dynamic deformations of buildings and other engineering structures is of great interest for many scientific and practical reasons. Such measurements provide information required for safe maintenance of the constructions being a subject of various excitations. At present one of the most commonly used technology for this purpose is the high-rate GNSS positioning. The application of GNSS technology with appropriate processing methodology may meet the specific requirements which result in extraction of information on dynamic dis placements and deformations of ground and engineering structures. The high temporal resolution and precision of GNSS phase observations predestine this technology to be applied to the most demanding applications in terms of ac curacy, availability and reliability. In this study we present preliminary results of application of precise GNSS positioning for detection of small scale (centimeter level) dynamic displacements. In the first part of work there are de scribed methodology and algorithms of precise coordinate estimation, involving both the relative positioning as well as the Precise Point Positioning technique. In the experiment both approaches were applied to monitor of antenna point variations on the basis of high-rate (20 Hz) observations processed in self-developed software. The dynamic dis placements were simulated using specially constructed device moving GNSS antenna with dedicated amplitude and frequency. The obtained results indicate on possibility of detection of dynamic GNSS antenna displacements even at the level of millimetres using relative positioning. Moreover, the Precise Point Positioning approach has also proved its applicability to detect high-rate small scale changes of the controlled site coordinates.
Keywords: high-rate GNSS positioning; satellite geodesy; metrology; displacements; RTK; PPP